Synergistic effect of graphene nanoplatelets and carbon black in multifunctional EPDM nanocomposites. (18th May 2016) - Valentini, L.; Bittolo Bon, S.; Lopez-Manchado, M.A.; Verdejo, R.; Pappalardo, L.; Bolognini, A.; Alvino, A.; Borsini, S.; Berardo, A.; Pugno, N.M.
Abstract: Ethylene–propylene–diene terpolymer rubber (EPDM)-based nanocomposites containing carbon black (CB), graphene nanoplatelets (GNPs), and mixtures of the two fillers were prepared. The influence of the relative amounts of the two fillers on the dynamic and static friction coefficients was examined. The static analysis of the coefficient of friction suggests that the partial substitution GNPs into the EPDM/CB blend did not produce a significant variation of the surface grip. The sample comprising EPDM/CB composite and an effective amount of GNPs dispersed in the matrix provides an increase of the thermal conductivity, damping (i. e. shock absorbing properties) and mechanical properties of the nanocomposites. The field-emission scanning electron microscopy and micro tomography analyses showed that the replacement of CB with GNPs reduces the CB aggregation and, hence, improving the percolation of the hybrid fillers and the interface resistance of the composite. The development of thermally conducting elastomeric nanocomposites could envisage their utilization in the processing of rubber blends satisfying the increasing demand to reduce both the duration of the vulcanization process and thus the cost of the vulcanized rubbers.